Entradas para armar a Bogotá imaginada - Silva, Armando (CIC. Cuadernos de Información y Comunicación, 2009)
This text is based upon the book of the same author Bogotà imagined (Bogotá, Taurus, 2005), which has been treated, transformed and selected to produce a present vision of the city in question. It is related with an international research about urban imaginaries, in which we worked with qualified interviews about the perception in groups of citizens with “different points of view”, as the method utilised required: they constituted different types of filters of perception by which the city was looked at and enunciated. AT the same time this perspective treats also other visual and historical and literary documents from which we can predict the formation of citizens imaginaries. There are also other cities, like Bogotá, which have been studied with the same methodology, and whose results Santillana Taurus Press in the series “Imagined Cities” has published that I direct.
Keywords: Imaginary cities; Urban imaginary; Identity; Culture; Qualitative research; Bogotá; Visual culture